DECISION SUPPORT SYSTEM IN CHOOSING THE BEST HONDA MOTORCYLE DEALER IN RIAU BY USING WEIGHTED PRODUCT METHOD(WP) - Wongso, Feri; Alexander, Alexander; Ameliza, Kiki (LPPM STMIK Dharmapala Riau, 2021)
A decision support system is used to find out the best dealer A decision support system is used to find out the best dealer in Riau with the WP (Weighted Product) method and a system is made to run it. In this system, the user will assign a weight value to each criterion and alternative.The data will be collected using interview and observation techniques. The analysis technique that will be used is to collect data, analyze data and draw conclusions from the results of research that has been carried out related to this research.The result of this research is a web-based system where the user can see the ranking based on the criteria and alternative values that the user inputs.